Regional Differences in Pathogen Prevalence and Defensive Reactions to the “Swine Flu” Outbreak among East Asians and Westerners - Hamamura, Takeshi; Park, J. (Evolutionary Psychology, 2010)
Research has found that contagion-minimizing behavioral tendencies are amplified in pathogen-prevalent regions. We investigated whether reactions to the “swine flu” outbreak of 2009 were stronger among East Asians than Westerners, populations residing in regions that now enjoy comparable advances in healthcare but that are characterized by relatively high and low historical pathogen prevalence, respectively. In a survey, East Asians reported greater concerns about infection, especially from foreigners. Analyses of international air travel data around the time of the outbreak provided corroborating evidence: Immediately following the outbreak, airports in the Asia–Pacific region lost more international traffic relative to their Western counterparts, and East Asian airlines reported greater declines in international traffic compared to Western airlines. These differences are unlikely to reflect objective threat posed by swine flu (whose casualties were concentrated in the Americas); rather, they appear to reflect culturally adapted behavioral patterns forged and sustained by regionally variable levels of pathogen prevalence.